Primary prevention of neural tube defects: data from the portuguese national registry of congenital anomalies (RENAC) - Braz, Paula (2016)
Background: In Portugal folic acid supplementation is recommended to start at least 2-3 months before conception for primary prevention of Neural Tube Defects. The aim of this study was to evaluate, within gestations with at least one congenital anomaly, possible association between maternal socio-demographic factors and the use of folic acid. Methods: Using data from the Portuguese national registry of congenital anomalies, for the 2004-2013 period, the association between folic acid use during pregnancy and maternal characteristics was studied using the chi-square test. Results: Considering all reported cases with congenital anomaly, the use of folic acid before conception was reported by 12.7% (n = 1233) of the women; 47.8% (n = 4623) started supplementation during the 1st trimester, 7% (n = 680) did not take folic acid and 32.5% (3143) of the records had no information on folic acid use. Women with professions that require higher academic differentiation started the use of supplements before pregnancy (p <0.001); women under 19 years old and with Arab ethnicity (p <0.001) did not take folic acid. Mothers with a previous pregnancy reported less use of folic acid (11.5% versus 14.7%) than mothers without a previous pregnancy (p <0.001). Conclusions: The results suggest some degree of association between maternal characteristics and use of folic acid. To increase the consumption of folic acid before pregnancy new measures are need to promote this primary prevention, among couples and health professionals. This study highlights some maternal characteristics and subgroups of mothers for who the measures should be reinforced.